2020
DOI: 10.3390/jimaging6030012
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake Actions Detection: An Improved Algorithm Toward Real-Time Analysis

Abstract: With the increase in life expectancy, one of the most important topic for scientific research, especially for the elderly, is good nutrition. In particular, with an advanced age and health issues because disorders such as Alzheimer and dementia, monitoring the subjects’ dietary habits to avoid excessive or poor nutrition is a critical role. Starting from an application aiming to monitor the food intake actions of people during a meal, already shown in a previously published paper, the present work describes so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Chang et al showed that these two could be combined to first detect the hand holding the cup, then detect the activity such as drinking or spoon holding [7]. Due to the common problem of occlusion with vision based approaches, Cippitell et al used a top down orientation with the Kinect placed on the ceiling to capture a meal intake [8], [9], [10]. Since the Microsoft Kinect does not function properly with a topdown orientation, they developed algorithms using a Self-Organized Map algorithm to track the person's movements.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al showed that these two could be combined to first detect the hand holding the cup, then detect the activity such as drinking or spoon holding [7]. Due to the common problem of occlusion with vision based approaches, Cippitell et al used a top down orientation with the Kinect placed on the ceiling to capture a meal intake [8], [9], [10]. Since the Microsoft Kinect does not function properly with a topdown orientation, they developed algorithms using a Self-Organized Map algorithm to track the person's movements.…”
Section: Previous Workmentioning
confidence: 99%
“…However, the dataset was limited, as it only included images of mealtime gestures. This work was expanded in [9] to improve the real-time capabilities which created a more automatic identification of the first and last frame of a food intake event. Cunha et al placed a Kinect in front of 3 elderly users consuming a meal.…”
Section: Previous Workmentioning
confidence: 99%
“…The SNAQ score was weakly correlated with the MNA-SF and MNA-LF scores (r=0.392 and r=0.380, respectively, p<0.0001 for both). Gambi, Ricciuti and De Santis (2020) proposed an application for monitoring an individual's eating habits during a meal, with the eating actions being assessed through in-depth image analysis. To enhance algorithmic performance and efficiency, the author's concept involves automating the process to identify various food-related actions.…”
Section: Related Workmentioning
confidence: 99%